Case Report: Clinical response to anaplastic lymphoma kinase inhibitor-based targeted therapy in uterine inflammatory myofibroblastic tumor harboring ALK-IGFBP5 fusion - Zhao, Ting; Zhang, Xiaowei; Liu, Xin; Ren, Min; Cheng, Yufan; Wang, Jian; Luo, Zhiguo (Frontiers in Oncology, 2023)
Background: Inflammatory myofibroblastic tumor (IMT) is a mesenchymal tumor with a prevalence ranging from 0.04% to 0.7% worldwide, in which, lung is the most common predilection site accounting for 33% followed by abdomen, pelvis, mesentery, and uterine. Approximately 50% of uterine IMTs present with anaplastic lymphoma kinase (ALK) positive along with ALK gene fusion, which lay a solid foundation for the development of ALK-based target therapy to optimize treatment strategies. Case presentation: We present a 57-year-old female presented with a slow-growing mass for over 10 years in the uterine, and then received surgical resection because of significant progressive enlargement of mass during follow-up. She was diagnosed with uterine leiomyosarcoma (LMS) with no further interventions until recurrence. We revised the diagnosis to uterine IMT according to diffuse ALK expression, ALK-IGFBP5 gene fusion, as well as the morphologic features of tumors by pathology consult. Based on these, we recommend an ALK tyrosine kinase inhibitor (TKI) treatment, crizotinib (250mg bid), and she achieved complete response (CR) with an 18 months of progression free survival (PFS) at least. We monitored the dynamics of target lesions and peripheral blood cells at regular intervals by CT scans and routine blood tests during the treatment process. We present a patient responses to ALK inhibitor based targeted therapy with uterine IMT harboring ALK-IGFBP5 fusion, and the neutrophil-to-lymphocyte ratio (NLR) is an effective indicator to predict prognosis.